Parodia czy kryptodialog? Na przykładzie Это было у моря Igora Siewierianina i Вы смотрели на море… Borysa Popławskiego - Ojcewicz, Grzegorz (Acta Polono-Ruthenica, 2011)
Author disputes with Helene Menegaldos idea, according to which Boris Poplavskis Вы смотрели на море is a parody of Igor Severyanins Это было у моря . Formal and semantic analysis of both texts presented in the article proves that Poplavskis poem cannot be a parody, a pastiche, or a travesty of Severyanins work but rather an encrypted dialogue perfectly blending into various intertextual contexts typical for the world literature that scrutinizes eternal questions. Poplavski didnt mock, he just bitterly commented in Bunins style on miniatu- re poem of Severyanin pointing at volatility of happiness, swift elapsing of love infatuations and also the role of chance which often decides about tragic human fate.